EDUKASI PEMANFAATAN SEDUHAN DAUN TEH HIJAU SEBAGAI ANTIKARIES DI DESA BOSA KEC. TAWAELI, SULAWESI TENGAH - R, Sririzqi Muthmainnah A.; Alaydrus, Syafika; Mariyani, Mariyani; Utami, Faikah Dyah; Djumiran, Sandra Sri Dewi; Tamuntuan, Annisa Fitria (Jurnal Abdi Insani, 2026)
Bosa Village is categorized as a 3T priority area (Frontier, Outermost, and Disadvantaged), resulting in a lack of dental health facilities and limited public knowledge regarding the dangers of dental caries, as well as a lack of understanding of utilizing plants for disease prevention. Shredded green tea leaves (Camellia sinensis) are a widely available commercial product that can be utilized for dental caries prevention due to their antibacterial properties. Therefore, the objective of this community service is to educate the public on dental caries prevention, specifically through the formulation of mouthwash from steeped green tea leaves to enhance knowledge of dental health maintenance using accessible products. The method employed was the lecture method, complemented by the distribution of brochures. This was followed by a recall of the material through a Q&A session. The results showed a significant improvement in the participants' competence between the pre-test and post-test. Although participants initially lacked understanding in several aspects, there was a substantial increase in comprehension following the post-test. This improvement was evident after the community of Bosa, Hamlet II, received education on utilizing green tea leaves as a mouthwash for dental caries prevention. Consequently, the community has begun to understand the prevention and maintenance of oral health, including the use of shredded green tea leaves as an anti-caries mouthwash.